A real‐world impact of cost‐effectiveness of pegylated interferon/ribavarin regimens on treatment‐naïve chronic hepatitis C patients in Taiwan. Issue 1 (18th November 2016) - Tsai, Pei‐Chien; Liu, Ta‐Wei; Hsieh, Meng‐Hsuan; Yeh, Ming‐Lun; Liang, Po‐Cheng; Lin, Yi‐Hung; Huang, Ching‐I; Huang, Chung‐Feng; Hsieh, Ming‐Yen; Hou, Nai‐Jen; Lin, Zu‐Yau; Chen, Shinn‐Cherng; et al.
Abstract: Treatments with pegylated interferon/ribavirin (PEG‐IFN/RBV) has been standard‐of‐care in patients with chronic hepatitis C virus (HCV) (CHC) infection and reimbursed in Taiwan. However, the actual cost‐effectiveness remains unclear. We aimed to evaluate a real‐world cost‐effectiveness for CHC patients treated with PEG‐IFN/RBV by using a clinical cohort with linkage to the National Health Insurance Research Database of Taiwan. The total and itemized medical‐care expenses of outpatient visits of 117 treatment‐naïve CHC patients with linkage to the two million sampling of the National Health Insurance Research Database were collected. Four components of costs were assessed, including antiviral agents, nonantiviral agents, laboratory testing and consultation costs. The cost per sustained virological response (SVR) achieved was calculated to evaluate the cost‐effectiveness. The average cost per treatment in 117 naïve Taiwanese CHC patients was 4620. With an overall SVR rate of 78.6%, the average cost per SVR was 5878. The average medical‐care cost per treatment for 52 Genotype 1 (G1) patients was 5133, including 4420 for antivirals, 380 for nonantivirals, 302 for laboratory, and 78 for consultation, compared to 4209, 3635, 317, 233, and 56 for 65 Genotype 2 (G2) patients. With an SVR rate at 67.3% for G1 and 87.7% for G2 patients, the cost per SVR achieved was significantly higher in G1 patients than those in G2 patients (7627 vs. 4799, p = 0.001). In the current study, we provided the real‐world cost‐effectiveness of PEG‐IFN/RBV for treatment‐naïve CHC patients. The genotype‐specific cost‐effectiveness could enhance decision‐making for policy‐makers in the coming era of directly acting antiviral therapy.